2015
DOI: 10.1016/s0185-2574(15)30005-8
|View full text |Cite
|
Sign up to set email alerts
|

The identity and worship of humain remains in rockshelter shrines among the Northern Lacandons of Mensabäk

Abstract: The present bioarchaeological and taphonomic investigation focuses on the skeletal remains deposited on surfaces of Lacandon rock-shelter sanctuaries around the Mensabäk lagoon in Chiapas (in particular the ones of Sak Tak and Mensabäk). The Lacandon locals still identify these remains with their ancestors and deities. Here we examine the minimum number of individuals, the age-at-death and sex profiles of those who comprise the assemblages, and their skeletal indications of physiological stress, trauma and cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…In a recent analysis of skeletal remains from a burial site in the Mensabak area of the Lacandon forests in Chiapas, Cucina et al (2015) concluded that the remains displayed evidence of violent deaths and wounds caused by metal weapons such as machetes and swords. Maxine Oland and Palka (2016, 480) note that the Mensabak region was an unconquered zone and that this type of violence was a result of the use of acquired metal tools in "local indigenous conflicts."…”
Section: Functional Uses Of European Goods By the Mayamentioning
confidence: 99%
“…In a recent analysis of skeletal remains from a burial site in the Mensabak area of the Lacandon forests in Chiapas, Cucina et al (2015) concluded that the remains displayed evidence of violent deaths and wounds caused by metal weapons such as machetes and swords. Maxine Oland and Palka (2016, 480) note that the Mensabak region was an unconquered zone and that this type of violence was a result of the use of acquired metal tools in "local indigenous conflicts."…”
Section: Functional Uses Of European Goods By the Mayamentioning
confidence: 99%
“…Their remains show violent deaths, such as a machete or sword cut to the face that cleanly removed the left side of a lower jawbone, a machete cut to a leg, a fall or blunt force trauma to the head, and scalping or flesh removal on the head with a metal knife (Cucina et al . 2015). This violence probably stemmed from local indigenous conflicts over the shifts in trade and the acquisition of metal tools, demarcation of agricultural land in a contested region, changes in demography and social organisation and political transformations following economic and demographic changes during the Spanish Colonial period (Hill 1996).…”
Section: Unconquered Zonementioning
confidence: 99%